Evidence level in the treatment of meningioma with focus on the comparison between surgery versus radiotherapy: a review - Pechlivanis, Ioannis; Wawrzyniak, Sebastian; Engelhardt, M.; Schmieder, Kirsten (Journal of neurosurgical sciences, 2011)
In the majority of cases surgery of intracranial meningioma is the primary treatment option. If tumor regrowth occurs or a tumor remnant is left, radiotherapy or radiosurgery are performed. Purpose of this review is to clarify the question, if evidence based data exists regarding the treatment of meningiomas with special focus on the efficacy of stereotactic radiosurgery/ radiotherapy (SRS/ SRT) compared to surgery. A systematic literature search in the most relevant medical databases was done. Primary studies and systematic review with focus on epidemiologic problems and different therapeutic approaches for the treatment of meningioma were included. Standardized data extraction was performed. A total of 31 publications were included. Information and results in the data published with a surgical focus vary strongly regarding the localization of the meningiomas. No randomized clinical trials or prospective cohort studies could be identified. Comparison between surgical and radiotherapeutic success rates was not clearly possible due to different outcome scales (Simpson grading versus tumor volume reduction) used. Progression free survival was ranging from 77% to 97% (complete surgical resection) and 82% to 97% (surgical resection and additional radiotherapeutical treatment) in publications not differentiating between the location of the meningioma. Although no clear evidence exists that one treatment is better than the other, in symptomatic meningioma surgery is considered to be the primary treatment, if the surgical risk is acceptable. Stereotactic radiosurgery and radiotherapy are reserved to locations (optic sheet, cavernous sinus), where surgical risk is expected to be higher.